The effect of spiral cold-bending manufacturing process on pipeline mechanical behavior. (July 2019) - Chatzopoulou, G.; Sarvanis, G.C.; Karamanos, S.A.; Mecozzi, E.; Hilgert, O.
Abstract: Large-diameter steel pipes, fabricated through the spiral-welding manufacturing process, are extensively used in onshore pipelines for the transmission of energy (hydrocarbon) and water resources. However, their use in demanding applications, such as geohazard areas or in offshore applications has been very limited. Safeguarding the structural integrity in such areas of those pipes requires an efficient strain-based design framework. Bending deformation capacity in the presence of internal pressure is the major loading case under geohazard actions, whereas external pressure capacity governs the mechanical design in moderate-deep offshore applications. To predict accurately the structural performance of spiral-welded pipes, the cold-bending manufacturing process should be taken into account. In the present paper, numerical models are developed simulating both the cold-bending process (decoiling and spiral bending) and the structural response of the pipe subjected to the loading conditions under consideration. The numerical modes have been verified against experimental results of spiral pipes conducted in the framework of a European research project. A parametric analysis is also conducted to examine the effect of spiral cold forming process on the structural behavior of spiral welded pipes. The results from the present study indicate that spiral-welded pipes can sustain significant amount of bending deformation and external pressure, in favor of their use in demanding onshore and moderately deep offshore pipeline applications.